2017
DOI: 10.15406/ijmboa.2017.02.00025
|View full text |Cite
|
Sign up to set email alerts
|

Study of Chemical Properties and Skin Tolerance Activity of Essential Oils Extracted from rosmarinus Officinalis and Populusalba

Abstract: There are many plants which were the subject of recent research in the fields pharmaceutical, cosmetic and agroalimentary because of their chemical composition and their several therapeutic activities. Among these plants, the species of Rosmarinus officinalis (rosemary) and Populus alba (white poplar).The present study aims to examine the yield and chemical properties of essential oil of rosemary and white poplar. Then, the test of skin tolerance of essential oils was conducted by the measuring of primary irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Low camphor content (3.845%) of R. officinalis essential oil might be responsible for absence of skin irritation since camphor is an irritant substance. This finding is in good agreement with that of Hamza et al (2017), who reported R. officinalis essential oil was non-irritant to the skin though the study was conducted in rat.…”
Section: Discussionsupporting
confidence: 92%
“…Low camphor content (3.845%) of R. officinalis essential oil might be responsible for absence of skin irritation since camphor is an irritant substance. This finding is in good agreement with that of Hamza et al (2017), who reported R. officinalis essential oil was non-irritant to the skin though the study was conducted in rat.…”
Section: Discussionsupporting
confidence: 92%